a(-2ab)=

Simple and best practice solution for a(-2ab)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a(-2ab)= equation:


Simplifying
a(-2ab) = 0

Remove parenthesis around (-2ab)
a * -2ab = 0

Reorder the terms for easier multiplication:
-2a * ab = 0

Multiply a * ab
-2a2b = 0

Solving
-2a2b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Divide each side by '-2'.
a2b = 0

Simplifying
a2b = 0

The solution to this equation could not be determined.

See similar equations:

| 54x+27y=x | | f(4x)=4x^2-11 | | 15-7p=-17p-15+10p | | 14x+71x=x | | 2vw-2w= | | 12x-(5x-12)=1+6x | | f(x)=2x^2-3x-1 | | 9+13j=13j+2 | | a(a^2-2ab+b^2)= | | 2(x+2)x=6 | | 0.5x-y=2 | | -4+10t=-2-10t+20t | | (X+93)=4x | | 17(9-x)-5=52 | | 0=-4u+4u | | 10g-3=10g-2 | | 7x-28=4 | | 7x-28=48 | | -(1-8x)=31+4x | | -5n+9-4=-5n+5 | | 14mn+18m= | | 9x-5=45 | | -7(2x-1)+5(3x-2)-7=4-9 | | 7+5k=5k+1 | | 2x-3=8x-3(1+2x) | | 3x+7=-2x+5 | | 0=-7s+7s | | 4x-35=3+10 | | 5x+bx=7 | | 3(1+5x)-1=-103 | | -8.6q+13.32=-18.4q+6.04+9.1q | | 5x+6x+7=5x-7 |

Equations solver categories